(untitled) (Conferencea, 2023)
Neuralgia (Greek - neuron - "nerve, nerve" + álgos - "pain") is a damage to peripheral nerves, characterized by painful attacks in the innervation zone of nerves. In contrast to neuritis, in neuralgia, there is no loss of movement and sensitivity, and there are no structural changes in the damaged nerve. Neuralgia mainly develops in the nerves that pass through narrow canals and holes.